Brown femininities and the queer erotics of indentureship. Issue 1 (8th July 2022) - Ellapen, Jordache A.
Abstract : This photo essay curates two interrelated bodies of creative work, Queering the Archive: Brown Bodies in Ecstasy (2013-ongoing) and The Brown Photo Album: An Archive of Feminist Futurities (2020), to explore the queer afterlives of indentureship in South Africa through the aesthetic realm. Queering the Archive and The Brown Photo Album are influenced by the photo archive of an Afro-Indian family from rural Kwa Zulu Natal. The curation of these two interrelated projects as this photo essay, Brown Femininities and the Queer Erotics of Indentureship, positions the maternal-feminine as central to the making of Afro-Indianness and to my own understanding of sexuality, beauty, pleasure and the erotic as informed by the home-space of the Afro-Indian family. This project maps my mother's desire to create a visual archive of the Afro-Indian woman in the immediate afterlife of indentureship onto my own desire to create a visual archive of the Afro-Indian queer experience in contemporary South Africa. The images translate the violence associate with the sugarcane plantations and indentureship into an aesthetic of pleasure where the past, present, and future as well as Black, Brown, and white bodies rub against and touch each other as an ongoing practice dedicated to re-imagining Afro-Indian intimacies and South African Blackness.